Evaluation of Rheum Aqueous Extract Effects on Inflammatory Biomarkers in Valproic Acid-Induced Hepatotoxicity in Rat Model - Abdulrahman, Raed Mohammed; Al-Qadhi, Huda Ibraheem; Ahmed, Watban Abdullah (Tikrit Journal of Pharmaceutical Sciences, 2024)
Background: Valproic acid (VPA) is a widely used anticonvulsant and mood stabilizer, but its clinical utility is often limited by hepatotoxicity. Rheum species, commonly known as rhubarb, have demonstrated hepatoprotective and anti-inflammatory properties, but their effects on inflammatory biomarkers in VPA-induced hepatotoxicity remain unclear. Objective: To evaluate the impact of Rheum aqueous extract on IL-6 and TNF-α levels in a rat model of VPA-induced hepatotoxicity, focusing on its potential hepatoprotective mechanisms. Methods: Thirty male albino rats were divided into five groups: Control, VPA-induced hepatotoxicity, L-carnitine, Rheum aqueous extract, and a combination of L-carnitine and Rheum extract. VPA was administered orally at 250 mg/kg/day for 20 days to induce hepatotoxicity. Treatments with L-carnitine (250 mg/kg/day) and Rheum extract (80 mg/kg/day) were initiated post-induction for 15 days. IL-6 and TNF-α levels were measured to assess inflammatory responses. Results: VPA treatment significantly increased IL-6 and TNF-α levels, indicating heightened inflammation. Both L-carnitine and Rheum extract independently reduced these inflammatory markers, with L-carnitine demonstrating a slightly stronger effect. However, combination therapy showed mixed outcomes: IL-6 levels were reduced, but TNF-α levels were unexpectedly elevated compared to the VPA group. Conclusion: L-carnitine and Rheum extract exhibit significant anti-inflammatory effects individually, reducing IL-6 and TNF-α levels in VPA-induced hepatotoxicity. However, their combination revealed potential adverse interactions, emphasizing the need for further research into their combined therapeutic application. These findings contribute to the understanding of natural and synthetic interventions for mitigating drug-induced liver injury.